2020
DOI: 10.1186/s12911-020-01288-7
|View full text |Cite
|
Sign up to set email alerts
|

Web-based interactive mapping from data dictionaries to ontologies, with an application to cancer registry

Abstract: Background The Kentucky Cancer Registry (KCR) is a central cancer registry for the state of Kentucky that receives data about incident cancer cases from all healthcare facilities in the state within 6 months of diagnosis. Similar to all other U.S. and Canadian cancer registries, KCR uses a data dictionary provided by the North American Association of Central Cancer Registries (NAACCR) for standardized data entry. The NAACCR data dictionary is not an ontological system. Mapping between the NAACC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…In terms of additional information use, future studies can consider additional ontologies, features, new data sources and features, demographic information, additional types of mappings or services, and multiple context information. First, Falkman et al [ 34 ] mentioned exploiting semantic Web-based foundation by using domain ontology and reasoning and by adding user and organizational ontologies; Tao et al [ 88 ] highlighted the need to allow ontology import in the Web ontology language; and Traverso et al [ 14 ] indicated using radiation oncology ontology “combined with other ontologies under development to combine and link DICOM information, clinical data and quantitative features computed on patients’ images and variables (p. 861)”. Second, Kim et al [ 73 ] suggested identifying and using additional features or entities (e.g., diseases, places, and time) that are important for determining “whether a report mentions an infectious disease outbreak (p. 12)” in deep learning models; Peral et al [ 89 ] indicated including new data sources like social networks; Chen et al [ 50 ] highlighted adding new features to facilitate annotating nodules on computed tomography images; Motlagh et al [ 53 ] mentioned adding features like NLP and the provision of consultancy services, psychotherapy, and medication.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of additional information use, future studies can consider additional ontologies, features, new data sources and features, demographic information, additional types of mappings or services, and multiple context information. First, Falkman et al [ 34 ] mentioned exploiting semantic Web-based foundation by using domain ontology and reasoning and by adding user and organizational ontologies; Tao et al [ 88 ] highlighted the need to allow ontology import in the Web ontology language; and Traverso et al [ 14 ] indicated using radiation oncology ontology “combined with other ontologies under development to combine and link DICOM information, clinical data and quantitative features computed on patients’ images and variables (p. 861)”. Second, Kim et al [ 73 ] suggested identifying and using additional features or entities (e.g., diseases, places, and time) that are important for determining “whether a report mentions an infectious disease outbreak (p. 12)” in deep learning models; Peral et al [ 89 ] indicated including new data sources like social networks; Chen et al [ 50 ] highlighted adding new features to facilitate annotating nodules on computed tomography images; Motlagh et al [ 53 ] mentioned adding features like NLP and the provision of consultancy services, psychotherapy, and medication.…”
Section: Resultsmentioning
confidence: 99%
“…The results of semantic enrichment in eHDPrep are critically dependent upon the ontology taken as input, and will likely suffer from a degree of annotation bias [76]. Also, mapping variables to ontology terms can be time-consuming and may require background knowledge of the variables if their labels are not self-explanatory; these issues may be mitigated by fuzzy string matching [77] and software interfaces, for example the UK National Health Service Digital SNOMED CT Browser [38]. Importantly, variables generated through semantic enrichment might not properly represent the quantitative relationship between their constituent variables due to unusual associations, such as J-curves [78].…”
Section: Discussionmentioning
confidence: 99%
“…This annotated value can then be further integrated into developing solutions and their overall context. In addition, ontologies can be directly used as vocabularies to support the organization of data according to known domain information [12]. One objective for this use is, for instance, allowing users to search data that has been annotated using ontologies in a database.…”
Section: Ontologies In Cancer Researchmentioning
confidence: 99%
“…Li et al [72], on the other hand, constructed a KG by first extracting knowledge triples from available data and then using these to construct a network for healthcare professionals that allows them to traverse this contextualized knowledge. Tao et al [12] developed a web-based system called Interactive Mapping Interface (IMI) to first map the data dictionary in use by the North American Association of Central Cancer Registries (NAACCR) to the NCIt with the final goal of facilitating the dissemination and reuse of North American cancer registries data. Chen et al [73] established a consensus knowledge for cancer hallmarks using functional annotations and gene set overlap, again aiming towards enabling the ability to compare data from different sources.…”
Section: Data Integrationmentioning
confidence: 99%